Re-interpreting relevant learning: an evaluative framework for secondary education in a global language. Issue 3 (2nd July 2016) - Barrett, Angeline M.; Bainton, David
ABSTRACT: The 2030 education goal privileges 'relevant learning outcomes' as the evaluative space for quality improvement. Whilst the goal was designed for global level monitoring, its influence cuts across different scales. Implementation of the goal involves reinterpreting 'relevant learning' at the local level. One way that small scale projects engage in the creative work of reinterpretation is through the design of their evaluative frameworks. We illustrate this with the example of an innovation in Tanzania that aimed to improve language and subject learning amongst lower secondary school students making the transition from using an African language, Kiswahili, to using a global language, English, as the language of instruction. The project developed a framework for evaluating learning processes and outcomes that was grounded in socio-cultural theories of learning. The framework was founded on an understanding of subject learning consistent with the purpose of sustainable development. Sustainable development is understood here as a process of social learning engaged through local responses to issues that have global reach. We conclude that implementing the 2030 education goals as part of a broader ambition towards sustainable development, demands reinterpretation of its targets in a way that makes explicit our underpinning theories of learning.